Experimental Study on the Influence of Oxygen Fraction in the Combustion Air on the Combustion Characteristics - P. Belohradsky; P. Skryja (Chemical Engineering Transactions, 2013)
The presented paper was focused on the experimental investigation of a promising combustion technology, namely the oxygen-enhanced combustion (OEC). This technology is used in those industrial heating applications that require increased productivity, higher heat transfer efficiency, improved flame characteristics, reduced equipment cost and last but not least improved product quality. However, there are potential problems associated with the use of OEC if the system is not properly designed, e.g. refractory or burner damage, non-uniform heating and/or increased pollutant emissions. The experimental study of OEC was carried out at the large-scale burner testing facility that enables to test the gaseous fuel burners, the liquid fuel burners and the combined burners up to the thermal input of 1800 kW. The combustion tests were performed with the experimental low-NOx type burner, namely the two-gas-staged burner. The oxygen content in the combustion air was increased by means of the oxygen injection directly into the incoming airstream before entering the burner. The aim of the tests was to assess the impact of oxidizer composition (the volume fraction of oxygen in the combustion air), burner thermal input and gas-staging on the characteristic combustion parameters including the concentration of nitrogen oxides in flue gas, the flue gas temperature, the heat flux to the combustion chamber wall, and lastly the flame stability and its dimensions.